CEO power and corporate social responsibility (CSR) disclosure: does stakeholder influence matter?. Issue 9 (21st September 2020) - Rashid, Afzalur; Shams, Syed; Bose, Sudipta; Khan, Habib
Abstract : Purpose: This study examines the association between Chief Executive Officer (CEO) power and the level of corporate social responsibility (CSR) disclosure, as well as the moderating role of stakeholder influence on this association. Design/methodology/approach: Using a sample of 986 Bangladeshi firm-year observations, this study uses a content analysis technique to develop a 24-item CSR disclosure index. The ordinary least squares regression method is used to estimate the research models, controlling for firm-specific factors that potentially affect the levels of CSR disclosure. Findings: The study findings indicate that CEO power is negatively associated with the level of CSR disclosure, and that the negative effects of CEO power on the level of CSR disclosure are attenuated by stakeholder influence. CEO power is documented as reducing the positive impact of CSR disclosure on a firm's financial performance, with this negative impact attenuated if stakeholders have greater influence on the firm. Practical implications: This study suggests that CEO power and stakeholder influence are important factors in determining firms' incentives to disclose CSR information. Both CEO power and stakeholder influence need to be considered in the CSR – firm performance nexus, given the mixed findings documented in the literature. Originality/value: This study makes a significant contribution to the literature on CSR practices by documenting that firms with a powerful CEO have lower levels of CSR disclosure, and that stakeholder influence affects CSR disclosure in the emerging economy context.